Analytic and Numerical Solutions of Time-Fractional Linear Schrödinger Equation - Edeki, S.O.; Akinlabi, G.O.; Adeosun, S.A. (Communications in Mathematics and Applications, 2016)
Fractional Schrödinger Equation is a basic equation in fractional quantum mechanics. In this paper, we consider both analytic and numerical solutions of time-fractional linear Schrödinger Equations. This is done via a proposed semi-analytical method upon the modification of the classical Differential Transformation Method (DTM). Some illustrative examples are used; the results obtained converge faster to their exact forms. This shows that this modified version is very efficient, and reliable, as less computational work is involved, even without given up accuracy. Therefore, it is strongly recommended for both linear and nonlinear time-fractional partial differential equations (PDEs) with applications in other areas of applied sciences, management, and finance.
Keywords: Time-fractional differential equations; Modified DTM; Schrödinger Equations; Analytical solutions.